Comprehensive Assessment of the Efficiency and Sustainability of the Regional Health Care System - Chereshnev, Valeriy A.; Krivenko, Natalya V.; Krylov, Victor G. (Economy of Regions, 2021)
Nowadays, the sustainability of the health care system is a relevant research topic. The works of Russian scientists demonstrate the lack of a systematic approach to determining the efficiency and sustainability of the Russian health care. International experience and the data of the Regional Office for Europe of the World Health Organization (WHO) show that, despite extensive research, efficiency indicators of the health care system have been insufficiently developed. Using the methods of multidimensional comparative analysis, determined factor analysis, structural analysis, expert assessment, statistical modelling and forecasting methods, we developed a methodology for the comprehensive assessment of the efficiency and sustainability of the regional health care system. The methodological toolkit includes the comprehensive assessment of the relative efficiency and relative sustainability of the regional health care system based on the established integral indicators. We tested this methodology on the example of the health care system of Sverdlovsk Oblast in the period 2017-2018. Integral indicators of the relative efficiency are directly influenced by the indicators of medical and social performance, which largely depend on the funding and management of the health care system. Simultaneously, the indicators of the relative efficiency can be high even if the indicators of the relative sustainability did not reach the established threshold. An integral indicator of the risk level considers the need to maintain the sustainability of the health care system for its functioning and development. Further, we constructed an interactive model for determining the risk zone and safe zone of the health care system. Due to its versatility, the proposed methodological toolkit allows an objective assessment of the efficiency and sustainability of the regional health care system.